LITERASI DIGITAL BAGI GURU SEKOLAH DASAR DI KABUPATEN BELU - Taty R. Koroh; Maxsel Koro; Adam B N Benu; Markus Sampe; Vera R Bulu; Sumardi W Ndolu (Pengabdian Masyarakat Ilmu Pendidikan, 2023)
The application of technology in learning is a must for teachers to respond to the challenges of changing times. The implementation of digital literacy training and assistance for elementary school teachers in the city of Atambua aims to train teachers in developing learning media and Quiz with Canva and Kahoot. The participants in this activity were 30 elementary school teachers spread across the city of Atambua. The result of this activity is an increase in teachers' skills in using Canva and Kahoot in developing learning media and quizzes for elementary school students as well as producing learning media products and practice questions in the form of quizzes.